Alternatívne prístupy k štúdiu územných identít obyvateľstva: Miera lokálneho povedomia na základe analýzy užívateľských profilov na sociálnej sieti - Richard, Nikischer (Lidé města, 2024)
Local consciousness represents the attachment of inhabitants to the smallest regional units (municipality, city district, neighbourhood, etc.); the concept of local consciousness thus falls under the broader concept of regional consciousness. From the viewpoint of social constructivism, regional consciousness is simultaneously both a source for regions and an output of regions; therefore, its scrutiny is an important component of the research on regional identities. Social network websites are an important channel of communication used by many individuals for the presentation of their personal identities, including their local identities. In this paper, the author analyses the degree of the local consciousness of the inhabitants of municipalities in Northern Slovakia, and does so on the basis of a conceptual analysis of the profiles of social network websites users. Based on the results of the analysis, the author explores the spatial disparities in the local consciousness of the inhabitants of Northern Slovakia, which is defined as the territory of the Zilina and Presov Regions. The article is therefore a demonstration of the utilisation of an alternative method of territorial consciousness research.